Association of novel measures of sleep disturbances with blood pressure: the Multi-Ethnic Study of Atherosclerosis. Issue 1 (22nd August 2019) - Kim, John S.; Azarbarzin, Ali; Wang, Rui; Djonlagic, Ina E.; Punjabi, Naresh M.; Zee, Phyllis C.; Koo, Brian B.; Soliman, Elsayed Z.; Younes, Magdy; Redline, Susan
Abstract : Background: Mechanisms underlying blood pressure (BP) changes in obstructive sleep apnoea (OSA) are incompletely understood. We assessed the associations between BP and selected polysomnography (PSG) traits: sleep depth, airflow limitation measurements and OSA-specific hypoxic burden. Methods: This cross-sectional analysis included 2055 participants from the Multi-Ethnic Study of Atherosclerosis who underwent PSG and BP measurements in 2010–2013. Sleep depth was assessed using the 'OR product', a continuous measure of arousability. Airflow limitation was assessed by duty cycle (Ti /Tt ) and % of breaths with flow limitation, and hypoxia by 'hypoxic burden'. Primary outcomes were medication-adjusted systolic BP (SBP) and diastolic BP (DBP). We used generalised linear models adjusted for age, sex, race/ethnicity, smoking, education, body mass index, alcohol use, periodic limb movements and alternative physiological disturbances. Results: The sample had a mean age of 68.4 years and apnoea–hypopnoea index of 14.8 events/hour. Sleep depth was not significantly associated with BP. Every 1 SD increment in log-transformed non-rapid eye movement duty cycle was associated with 0.9% decrease in SBP (95% CI: 0.1% to 1.6%), even after adjusting for sleep depth and hypoxic burden. Every 1 SD increment in log-transformed hypoxic burden was associated with a 1.1% increase in SBP (95% CI: 0.1% to 2.1%) and 1.9% increase in DBP (95% CI: 1.0% to 2.8%) among those not using hypertension medications. Conclusions: Higher duty cycle was associated with lower SBP overall and hypoxic burden with higher SBP and DBP among non-BP medication users. These findings suggest changes in both respiratory effort and oxygenation during sleep influence BP.